2007
DOI: 10.1111/j.1365-3156.2007.01937.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low‐cost irrigation methods on microbial contamination of lettuce irrigated with untreated wastewater

Abstract: Summaryobjective To assess the effectiveness of simple irrigation methods such as drip irrigation kits, furrow irrigation and use of watering cans in reducing contamination of lettuce irrigated with polluted water in urban farming in Ghana.methods Trials on drip kits, furrow irrigation and watering cans were conducted with urban vegetable farmers. Trials were arranged in a completely randomised block design with each plot having all three irrigation methods tested. This was conducted in both dry and wet season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 17 publications
0
36
1
Order By: Relevance
“…So a total cumulative reduction of 3.92 log units for thermo-tolerant coliforms and 3.2 log units of helminth eggs was achieved. The reduction could be even higher if water treatment methods like sedimentation ponds and better irrigation methods like drip irrigation could be used, as demonstrated in earlier studies done in Kumasi (see Keraita et al, 2007a;2008a). recorded high levels of coliform bacteria similar to water from urban streams that appeared to be physically dirty.…”
Section: Cumulative Effect Of Risk Reduction Strategies For Cabbage Imentioning
confidence: 71%
See 1 more Smart Citation
“…So a total cumulative reduction of 3.92 log units for thermo-tolerant coliforms and 3.2 log units of helminth eggs was achieved. The reduction could be even higher if water treatment methods like sedimentation ponds and better irrigation methods like drip irrigation could be used, as demonstrated in earlier studies done in Kumasi (see Keraita et al, 2007a;2008a). recorded high levels of coliform bacteria similar to water from urban streams that appeared to be physically dirty.…”
Section: Cumulative Effect Of Risk Reduction Strategies For Cabbage Imentioning
confidence: 71%
“…Nevertheless, low-cost drip irrigation techniques like bucket drip kits from Chapin Watermatics (USA) and International Development Enterprises (IDE, India) offer more potential for use in low-income countries, and are now available on the market (Kay, 2001). Our study in Ghana using bucket drip kits show even higher reduction in contamination (up to 6 log units), especially during the dry season (Keraita et al, 2007a). The same study in Ghana also showed great potential for modifying traditional systems, in this case lowering watering cans to reduce splashing of contaminated soils onto crops.…”
Section: Farm-based Practicesmentioning
confidence: 74%
“…In Zimbabwe, Mutengu et al ( 2007 ) found that the public health risk of soil contamination by heavy metals and health risks by plant uptake of heavy metals seemed to be negligible probably because of the source of effl uent. Keraita et al ( 2007a ) carried out a study on untreated wastewater irrigation in Ghana and their results showed that cheaper and simple irrigation methods need to be developed and assessed in order to reduce health risks. Such methods are more likely to succeed in informal urban irrigation settings, where low tenure security prevents farmers from investing in sophisticated methods or on-site treatment ponds.…”
Section: Healthmentioning
confidence: 99%
“…Fresh produce grown in such ways are often contaminated [4] with e.g. helminthes eggs (Amoah et al, 2006;Keraita et al, 2008a), as well as soil, as a consequence of repeated application of polluted water (Keraita et al, 2007a). Several constraints hamper strategies to reduce microbial risk.…”
Section: Farm Animals and Produce Safety Issuesmentioning
confidence: 99%
“…Several constraints hamper strategies to reduce microbial risk. The limited land space available [5] proscribes the installation of on-farm water treatment ponds [6] (Keraita et al, 2008a); the limited investment capacity of the farmers [7] prohibits the acquisition of efficient water treatment systems [8] or drip irrigation equipment that would reduce contamination of the produce (Keraita et al, 2007a); the need for intensive production [9] and the lack of organized marketing systems [10] makes a safe planning of irrigation difficult [11], such as interrupting irrigation with unsafe water a few days before harvest (Keraita et al, 2007b). In addition, the market for this urban production lack commercial incentive for safer production practices (Keraita et al, 2008b;Levasseur et al, 2007).…”
Section: Farm Animals and Produce Safety Issuesmentioning
confidence: 99%